Implementation of Roles and Functions of Case Managers - Fransisca Sri Susilaningsih; Brilyan Anindya Dayfi; Kurniawan Yudianto (Faculty of Nursing Universitas Padjadjaran, 2018)
Case management is an intervention strategy used by health care providers and systems to support clients, coordinate health services, and facilitate results in both price and quality. In this model of care, the case manager plays an important role in ensuring that the case management service flow is well implemented. This study aims to see how the role of case managers in carrying out their functions such as utility assessment, planning, facilitation and advocacy, service coordination, evaluation, and post-discharge follow-up. The research method used is the mixed method sequential exploratory design. This method explores the work experience of a case manager in the field, then composes a measuring instrument, and then seeks to quantify the role and function of the case manager. The population in this study was the case managers in the Kemuning and Fresia Building at Dr. Hasan Sadikin General Hospital Bandung amounting to 36 people. The research sample was divided into two, in the qualitative stage the number of participants as many as 5 people was determined by purposive sampling technique, and the quantitative stage used a total sampling of 36 people. The results showed that the qualitative analysis of the assessment function identified indicators of ability to collect data, analysis, and stratification of patients; in the planning function the ability to determine goals, take joint decisions and identify problems were identified; in the facilitation function and advocacy, the ability to be identified as an educator, protector of patient rights and solution provider were identified; in the service coordination function, the ability for team communication and communication between lines were identified; in the evaluation function the ability to evaluate patients and self-evaluation were identified; and in the post-discharge follow-up function the ability related to continuity of service was identified. In the implementation, the case manager carries out those functions, 4 functions are still carried out improperly by most respondents such as the joint decision making, team communication, patient evaluation, and self-evaluation.